Corrigendum to “Computational simulation of surface tension and gravitation-induced convective flow of a nanoliquid with cross-diffusion: An optimization procedure” [applied mathematics and computation 425 (2022) 127108] - Mackolil, Joby; Mahanthesh, B. (Applied mathematics and computation, 2024)
This corrigendum addresses both the physical configuration and certain typographical errors in [1] to improve clarity. These corrections do not impact the originality, results, or mathematical validity of [1].